New Directions in Macroeconomics - Asad Zaman (International Econometric Review (IER), 2020)
The glaring failure of modern macroeconomics to predict the Global Financial Crisis, and to provide remedies for the Great Recession which followed, has led to renewed interest in alternative approaches to Macroeconomics. There is huge amount of ongoing work aimed at creating a Macroeconomics for the 21st Century. The task is of the highest priority, as failures of economic theory have led to misery for millions. Wrong measures of GDP, and cost-benefit calculation which fail to account for environmental costs, and prioritize private profits over social welfare, have created a climate catastrophe which threatens to destroy the planet. In accordance with the importance of this task, we are expanding the scope of this journal, to cover all new approaches to economics, which fall outside of the boxes of conventional macro, micro, and econometrics of the 20th Century. This article outlines seven broad categories of research directions, and four different methodological principles which fall outside the boundaries of the conventional approach, and offer promise for building a Macroeconomics for the 21st Century. We hope to invite contributions in these areas for future issues.
Keywords: B41; B50; 330; Political Economy; Complexity Economics; Ecological Economics; PostKeynesian Economics; Islamic Economics